Home to Work: Motherhood and Politics of Industrial Homework in the United States - Zeytimoglu, Izik Urla (Relations industrielles / Industrial Relations, 1995)
The article reviews the book, "Home to Work: Motherhood and Politics of Industrial Homework in the United States," by Eileen Boris.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Employment; History; Home workers; Labor Unions; Law; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Social sciences; Women; Work at home; Working mothers